2016
DOI: 10.3130/jaabe.15.433
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Utilization of Public Space in Rusunawa Mariso, Makassar – Indonesia

Abstract: Rusunawa was built to anticipate the needs of low-income residents for affordable urban homes. This study identifies its diversity and designed function and evaluates the existing utilization of public spaces in Rusunawa. Furthermore, it identifies the underlying reasons for them. Structured observation is applied through person-centered mapping, with a combination of structured and unstructured interviews. Public spaces in Rusunawa can be categorized into eight locations (corridor, main stair, emergency stair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…When investigating how space influences social interaction, most studies focused on the space, such as through space syntax (e.g., El-Darwish, 2022;Ridwana et al, 2018) or personcentred mapping in a short timeframe, as demonstrated by Bunawardi et al (2016). However, social capital is rooted in the individual and then influenced by the surroundings, including the built environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When investigating how space influences social interaction, most studies focused on the space, such as through space syntax (e.g., El-Darwish, 2022;Ridwana et al, 2018) or personcentred mapping in a short timeframe, as demonstrated by Bunawardi et al (2016). However, social capital is rooted in the individual and then influenced by the surroundings, including the built environment.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, even in the case of middle-rise Rusunawa, only some studies explore the relationship between space and social interaction and capital. For example, Bunawardi et al (2016) discussed the type of social interaction and the diversity of social demographics in different space configurations. In addition, Wijayanti et al (2019) also highlight the importance of spaces as the nexus of civic activities to foster social capital.…”
Section: Introductionmentioning
confidence: 99%
“…Housing should provide open space as a means of socializing residents housing. Comfortable, healthy, and affordable city residence is a critical issue in every developing country, particularly in urban areas (Bunawardi, Suzuki, & Yuasa, 2016).…”
Section: One Of the Facilities In Housing An Open Spacementioning
confidence: 99%
“…According to BPS (Badan Pusat Statistik) Indonesia, housing development in Indonesia has reached 15 million units in around 2014-2015. The condition can be exacerbated by the growth of about 800,000 new households each year (Bunawardi et al, 2016). To overcome, the Indonesian government has targeted 1 million dwellings per year starting from 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, which tends to be hot and humid, most of the dwellings that are now developed are medium and tall buildings. Indonesia generally has three types of apartments/flats, namely simple flats (Rusun), medium flats (Apartments), and luxury flats (Kondomium) (Bunawardi et al, 2016). Rusun itself can be categorized as Affordable Housing (AH).…”
Section: Introductionmentioning
confidence: 99%